Friendship and the Future of Interreligious Cooperation - Paul Martens (International Journal of Interreligious and Intercultural Studies, 2022)
To face contemporary global challenges like climate change, interreligious cooperation that extends beyond mere dialogue or declaration will become increasingly important. Drawing upon Aristotle’s multi-layered description of friendship and recognizing that nearly all the world’s population is already implicitly involved in interreligious friendships of utility framed and enabled by global neoliberalism, this article argues for a constructive account of interreligious cooperation built upon interreligious friendship. This cooperation is localized, flexible, and open to participation by all in the community without requiring predetermined agreement or universally binding norms.